367 Can We Justify Routine Group & Screen Testing Prior to Appendicectomies? - A Single Centre Analysis. (19th August 2022) - Deb, R; Deb, G; Pore, N; Sheth, H; Raje, D
Abstract: Aim: Numerous sources have suggested that routine preoperative Group & Screen (G&S) testing prior to cholecystectomies 1–4, breast surgery 5 and gynaecological procedures including Caesarean sections 6 may be unnecessary because perioperative blood transfusion incidence remains low. This project aimed to understand whether routine pre-appendicectomy G&S testing can be justified by analysing blood transfusion incidence for appendicectomies completed at our hospital. To further comment on their relevance to clinical practice, we also aimed to investigate any potential delay to surgery that G&S tests may pose, and their cost implications. Method: For all appendicectomies undertaken at our hospital from 2018 to 2021 (n = 257), we noted if the patient received a blood transfusion anytime during their admission. The date and time of G&S sample collection and of the surgery were recorded, including any documentation of delays to surgery. Results: 0% of appendicectomies between 2018 – 2021 required a blood transfusion during the admission. On average, 3.9% of appendicectomies per year were delayed due to preoperative G&S testing with an average delay to surgery of 78.71 minutes. The total cost of G&S tests undertaken for appendicectomy patients between 2018 – 2021 was £5768.03. Conclusions: It is difficult to justify routine pre-appendicectomy G&S testing when our data suggests such a low risk of blood loss necessitating transfusion, and that these tests delay treatment. This may warrant pre-appendicectomy risk stratification to streamline G&S testing. Additionally, should an emergency occur, uncrossmatched blood is readily accessible and poses minimal risk to patients 7 .